Real-time measurement of methane in a turbulent atmosphere over kilometer long paths with denoising methods. (15th January 2021) - Xia, Jinbao; Feng, Chao; Zhu, Feng; Zhang, Sasa; Kolomenskii, Alexandre A.; Dong, Jian; Schuessler, Hans A.
Highlights: Long-range sensor with wavelength modulation spectroscopy was built and tested. The signal processing with Kalman filtering and wavelet denoising were compared. The detection limit of 4.7 ppb with 0.25 s integration time was achieved. Abstract: A wavelength modulation spectroscopy (WMS) setup for long-range methane measurements in the atmosphere over distances of kilometers was developed. To overcome the influence on the signal from noise, random factors and air turbulence, we applied denoising processing methods, which were analyzed and compared. The real-time digital Kalman filter was selected and utilized, improving the detection limit for methane sensing from 60 ppb with integration time of 60 s to 2 ppb with integration time of 1 s. To our knowledge, this is the first realization of such highly sensitive and yet simple sensor by combining the real-time filter and WMS. This approach opens the possibility to replace much more complicated instruments in sensitive measurements of trace gases when evaluating the experimental data with the Kalman filter.